2021
DOI: 10.1002/eng2.12464
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of continuous variable crown work roll shifting strategy using k‐nearest neighbors algorithm for hot strip rolling mill

Abstract: Appropriate work roll shifting strategy in the finishing hot strip mill can make roll wear uniform and contour smooth. To eliminate the problem of roll shifting position duplication due to available roll shifting strategy, the optimized work roll shifting strategy is proposed in the hot strip rolling mill with continuous variable crown work rolls, using the k-nearest neighbors algorithm. The self-perpetuating parameter is used to describe the concentrated wear of the work roll. The position repeated parameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…Stands 4-6 exhibited a smooth wear distribution along the roll width (Figure 7), indicating that the shifting strategy produced proper wear distribution, with the absence of sharp variations in the roll wear profile [16]. These observations are consistent with the findings reported in previous studies [5,16], which suggested that the proper shifting setup significantly affects the wear in the strip edge zones, preventing anomalies in work roll contours. This analysis also indicates that there are improvement opportunities using this simulation tool for further optimizations on shifting setup.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Stands 4-6 exhibited a smooth wear distribution along the roll width (Figure 7), indicating that the shifting strategy produced proper wear distribution, with the absence of sharp variations in the roll wear profile [16]. These observations are consistent with the findings reported in previous studies [5,16], which suggested that the proper shifting setup significantly affects the wear in the strip edge zones, preventing anomalies in work roll contours. This analysis also indicates that there are improvement opportunities using this simulation tool for further optimizations on shifting setup.…”
Section: Discussionsupporting
confidence: 89%
“…It is not an easy task to control both strip profile and flatness, particularly in a tandem hot strip mill that must deal with multiple targets and interactions such as control of the heterogeneous plastic deformation in roll bites, control of the affinity of the incoming transverse strip profile with the outgoing one; deal with non-linear evolution of roll thermal expansion, elastic deformation and wearing [2,3]. There are several models to calculate the relationship between flatness and thickness profile in a tandem finishing mill [1][2][3][4][5][6]. All these calculations are heavily influenced by the ground roll profiles for each stand of the rolling process.…”
Section: Introductionmentioning
confidence: 99%
“…Yamaguchi et al [15] provided a method for the work roll shifting mode using an evaluation function. Gong et al [16] proposed an optimized work roll shifting strategy with CVC rolls according to k -nearest neighbours algorithm. Cao et al [17] proposed a variable stroke and step shifting strategy to get the work roll wear smoothly.…”
Section: Introductionmentioning
confidence: 99%